Improved efficiency of Sb2Se3/CdS thin-film solar cells: The effect of low-temperature pre-annealing of the absorbers. (October 2018) - Lee, Dajeong; Cho, Jae Yu; Heo, Jaeyeong
Graphical abstract: Highlights: Thin films of antimony selenide (Sb2 Se3 ) were deposited via thermal evaporation. The duration of pre-annealing at 100 °C influenced the morphology of Sb2 Se3 films. Pre-annealing for 40 min resulted in optimized crystallinity of Sb2 Se3. The highest efficiency of 1.47% is achieved for the Sb2 Se3 /CdS heterojunction. Abstract: Sb2 Se3 is one of the alternative absorber materials for thin-film solar cells (TFSCs) comprising non-toxic and low-cost elements. The duration of pre-annealing at 100 °C prior to rapid thermal annealing (RTA) influenced the final morphology, crystallinity, and preferred orientation of thermally evaporated Sb2 Se3 . Pre-annealing for 40 min promoted the crystallization of pure Sb2 Se3 phase following RTA; however, a long pre-annealing time such as 100 min rendered morphology similar to that of the reference absorber that was not pre-annealed, as ascertained by detailed scanning electron microscopy, X-ray diffraction, and Raman spectroscopic analyses. Furthermore, Sb2 Se3 /CdS TFSCs were fabricated with Sb2 Se3 pre-annealed for various durations. The highest efficiency of 1.47% was achieved for the optimized 40-min pre-annealed absorber, enabling a smooth current flow. Our results emphasize the detailed optimization of pre-annealing time for achieving efficient TFSCs.